Season and temperature do not affect cumulative live birth rate and time to live birth in in vitro fertilization - Du, Mingze; Zhang, Junwei; Wei, Zhancai; Li, Li; Liu, Xinmi; Liu, Manman; Wang, Xingling; Guan, Yichun (Frontiers in Endocrinology, 2023)
Objective: To explore whether season and temperature on oocyte retrieval day affect the cumulative live birth rate and time to live birth. Methods: This was a retrospective cohort study. A total of 14420 oocyte retrieval cycles from October 2015 to September 2019. According to the date of oocyte retrieval, the patients were divided into four groups (Spring(n=3634)；Summer(n=4414)；Autumn(n=3706)；Winter(n=2666)). The primary outcome measures were cumulative live birth rate and time to live birth. The secondary outcome measures included the number of oocytes retrieved, number of 2PN, number of available embryos and number of high-quality embryos. Results:The number of oocytes retrieved was similar among the groups. Other outcomes, including the number of 2PN (P=0.02), number of available embryos (p=0.04), and number of high-quality embryos (p<0.01) were different among the groups. The quality of embryos in summer was relatively poor. There were no differences between the four groups in terms of cumulative live birth rate (P=0.17) or time to live birth (P=0.08). After adjusting for confounding factors by binary logistic regression, temperature (P=0.80) , season (P=0.47) and duration of sunshine(P=0.46) had no effect on cumulative live births. Only maternal age (P<0.01) and basal FSH (P<0.01) had an effect on cumulative live births. Cox regression analysis suggested no effect of season(P=0.18) and temperature(P=0.89) on time to live birth. Maternal age did have an effect on time to live birth (P<0.01). Conclusion: Although season has an effect on the embryo, there was no evidence that season or temperature affect the cumulative live birth rate or time to live birth. It is not necessary to select a specific season when preparing for IVF.